Analysis of the Implementation of Shear Wall/Core Wall Construction as the Implementation of Practical Work at the KYO Society Project, Surabaya - Irwanto, Bramantyo Haedar Hugo; Zulfikar, Anggi Rahmad (Universitas Kristen Cipta Wacana, 2025)
This study aims to systematically describe the implementation process of Shear Wall/Core Wall structural works, quality management (Quality Control), and the application of Occupational Health and Safety (OHS) at the KYO Society Apartment Development Project in Surabaya, carried out by PT Wijaya Karya Bangunan Gedung Tbk. The research employed a descriptive qualitative approach through direct field observations, project document analysis, informal interviews, and the collection of primary and secondary data during the industrial internship period. The data analyzed included stages of structural work (formwork installation, reinforcement installation, concrete casting, and dismantling), work scheduling, equipment utilization, work volume records, and OHS documents such as Job Safety Analysis (JSA), lists of Personal Protective Equipment (PPE), and emergency response procedures.vThe results indicate that the implementation of Shear Wall/Core Wall works has complied with the shop drawings and the project’s Standard Operating Procedures (SOPs). However, several on-site constraints were identified, such as adjustments to concrete casting schedules and equipment availability, which required technical coordination. From a Quality Control perspective, material inspection, dimensional checks, and concrete quality control were conducted in accordance with established procedures. The implementation of OHS at the project site has generally been well executed, as evidenced by the use of PPE, regular toolbox meetings, the installation of safety signage, and the presence of emergency response flowcharts. Nevertheless, supervision of potential hazards and worker discipline still require improvement. Overall, this study provides a comprehensive overview of structural work processes and OHS systems in high-rise building construction projects, which can serve as a reference for improving project management and occupational safety in the future.